1983
DOI: 10.1056/nejm198306093082304
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Cholera in Breast-Fed Children by Antibodies in Breast Milk

Abstract: We performed a prospective study to examine whether the IgA antibodies against cholera that are present in breast milk protect breast-fed infants and children against colonization with Vibrio cholerae 01 and disease. Among families of patients with cholera, we collected breast milk from mothers who had not had diarrhea in the previous week and monitored them and their breast-fed children for cholera colonization and diarrhea for 10 days. Breast milk was assayed for IgA antibodies to cholera toxin and lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(118 citation statements)
references
References 18 publications
4
114
0
Order By: Relevance
“…The lack of clinical symptoms in the presence of a pathogenic agent could be due to active immunity produced by previous contact with similar organisms or, as has been shown in the case of cholera (Glass et al 1983), to passive immunity produced by specific antibodies present in the breast milk 99 % of these children received from birth. What does not seem conceivable with these findings is that a micro-organism can produce diarrhoea only in children of certain age groups without the active participation of the host.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of clinical symptoms in the presence of a pathogenic agent could be due to active immunity produced by previous contact with similar organisms or, as has been shown in the case of cholera (Glass et al 1983), to passive immunity produced by specific antibodies present in the breast milk 99 % of these children received from birth. What does not seem conceivable with these findings is that a micro-organism can produce diarrhoea only in children of certain age groups without the active participation of the host.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of poliovirus, significantly higher IgA titers were documented in breast milk samples from unvaccinated women from Pakistan compared with vaccinated women from Japan or Sweden in the early 1990s [59], and it is likely that similar discrepancies between endemic and nonendemic settings persist today. Antibodies against cholera toxin and lipopolysaccharide are also common among mothers in low-income countries [60].…”
Section: Breastfeedingmentioning
confidence: 99%
“…In the case of poliovirus, significantly higher IgA titers were documented in breast milk samples from unvaccinated women from Pakistan compared with vaccinated women from Japan or Sweden in the early 1990s [59], and it is likely that similar discrepancies between endemic and nonendemic settings persist today. Antibodies against cholera toxin and lipopolysaccharide are also common among mothers in low-income countries [60].Findings regarding the overall impact of breastfeeding on oral vaccine performance are notable for their lack of consistency. The effects of breastfeeding are confounded with those of transplacental antibodies owing to the close correlation between antibody titers in maternal breast milk and serum [45].…”
mentioning
confidence: 99%
“…3 Protection against diarrheal bacteria and their toxins is offered by secretory IgA (sIgA) antibodies of milk along with the study of infections with the origin of enterotoxigenic E. coli, Shigella, Vibrio cholerae, and Giardia lamblia. 4 Recently, it was shown that the human anti secretory peptide factor, when induced in breast milk, had more protective activity against acute diarrhea than chronic diarrhea. 5,6 A study in Mexico has revealed that breastfeeding is associated with 5-fold lower risk of diarrhea with G. lamblia agent in comparison to feeding without breast milk, and 1.8-fold lower risk with incomplete breastfeeding.…”
Section: Introductionmentioning
confidence: 99%